MODEL PEMBELAJARAN ATIVITY MARKET PLACE DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Kholidatur Rodiyah, Siti; Badriyah, Laila (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2025)
This research discusses of a market place activity learning model in Islamic religious education learning. This research is a literature review type of research, namely research carried out using the library method. The data analysis technique was carried out using a descriptive comparative analysis approach regarding the development of Islamic religious education learning using the market place activity learning model. The results of this research show a descriptive understanding of the market place activity learning model. market place learning model in Islamic religious education learning design. Implementation of learning using the market place activity learning model has several stages, namely planning, implementation and assessment. Evaluation of Islamic religious education learning using the market place model achieved up to 85% of the minimum completeness criteria. There are several factors supporting the method, namely leadership factors from a school principal, support factors from parents, and ability factors from a teacher. There are several inhibiting factors, namely differences in the character of the students, feelings of doubt from the students, feelings of embarrassment from the students, requiring a long time and answers from the students that are less relevant. The advantages of the market place activity method can increase